Site occupancy of select mammals in the tropical forest of Eastern Himalaya - Ahmad, Arif; Gopi, Govindan Veeraswami (Frontiers in Ecology and Evolution, 2024)
Terrestrial mammals are a key component of tropical forest communities, representing this biome's rich and functionally diverse component. Unfortunately, they face significant threats worldwide, including hunting, habitat loss, and fragmentation. As human-altered landscapes spread in the tropics, it is critical to understand how these changes affect mammal communities to design relevant conservation interventions. The tropical forest of northeast India is a biodiversity hotspot that harbors a diverse assemblage of mammalian fauna. The most significant challenge they face is anthropogenic activities, resulting in the shrinkage and fragmentation of forests and wildlife habitats. We carried out a systematic camera trapping monitoring to evaluate the status and distribution of mammals in Mehao Wildlife Sanctuary (WLS). We used single-season occupancy models to determine the factors affecting mammalian species' detection probability and space use in the landscape. In our study, we recorded 27 mammalian species. Twelve species are recognized as "threatened" on the IUCN Red List. We detected clouded leopard (Neofelis nebulosa), marbled cat (Pardofelis marmorata), Gongshan muntjac (Muntiacus gongshanensis), red goral (Naemorhedus baileyi), Mishmi takin (Budorcas taxicolor), and sambar (Rusa unicolor). Still, they were found to be rare in the landscape. We also report the first record of Asiatic brush-tailed porcupine from Mehao. The occupancy results revealed that all species preferred undisturbed forest habitats. Mainland serow (Capricornis sumatraensis) occupying most of the sanctuary's area, followed by northern red muntjac (Muntiacus vaginalis), yellow-throated marten (Martes flavigula), and masked palm civet (Paguma larvata). The mammals exhibited variable responses to various ecological and anthropogenic covariates, highlighting the need for species-specific management strategies in addition to a landscape-scale conservation approach. The results of this study highlight the importance of managing and protecting rare and elusive mammalian species in and around Mehao WLS.